Observation of B_{c}^{+}→Dh^{+}h^{-} Decays. - Aaij,R; Abdelmotteleb,ASW; Abellan,Beteta C; Abudinén,F; Ackernley,T; Adefisoye,AA; Adeva,B; Adinolfi,M; Adlarson,P; Agapopoulou,C; Aidala,CA; Ajaltouni,Z; et al. (Phys Rev Lett, 2026)
Searches are presented for B_{c}^{+}→Dh^{+}h^{-} decays, where D is a charmed meson and h^{±} is a charged pion or kaon, using pp collision data collected by the LHCb experiment corresponding to an integrated luminosity of 9  fb^{-1}. The decays B_{c}^{+}→D^{+}K^{+}π^{-}, B_{c}^{+}→D^{+}K^{+}π^{-}, and B_{c}^{+}→D_{s}^{+}K^{+}K^{-} are observed for the first time. Their branching fractions, expressed as ratios relative to that of the B_{c}^{+}→B_{s}^{0}π^{+} decay, are determined to be R(B_{c}^{+}→D^{+}K^{+}π^{-})=(1.96±0.23±0.08±0.10)×10^{-3}, R(B_{c}^{+}→D^{+}K^{+}π^{-})=(3.67±0.55±0.24±0.20)×10^{-3}, R(B_{c}^{+}→D_{s}^{+}K^{+}K^{-})=(1.61±0.35±0.13±0.07)×10^{-3}, where the first uncertainty is statistical, the second is systematic, and the third is due to the limited precision on the D-meson branching fractions. The decay channels proceed primarily through excited K^{0} or D^{0} resonances or mesons, and open a new avenue for studies of charge-parity violation in beauty mesons.